2021
DOI: 10.5430/ijfr.v12n1p348
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Financial Intermediaries on Nigerian Economic Growth

Abstract: This paper empirically investigated the impact of financial intermediation of economic growth in Nigeria. Quarterly time series data generated from the World Bank Development indicator and the Nigerian Bureau of Statistic for the periods 1994Q1 to 2018q4 were used for the analysis, and Ordinary Least Squares (OLS) regression technique was adopted for the estimation of the hypotheses. Per-capita GDP was used as a measure of economic growth, while bank deposit, bank credit and bank reserves are measures of finan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Commercial banks play the critical role of financial intermediation whereby they facilitate flow of funds between persons with financial surplus, mainly savers and those with financial deficit mainly borrowers and investors (Manasseh et al, 2021). They aggregate funds on behalf of the borrowers and investors while also facilitating settlement of business transactions.…”
Section: Issn: 2616-4965 11 Background Of the Studymentioning
confidence: 99%
“…Commercial banks play the critical role of financial intermediation whereby they facilitate flow of funds between persons with financial surplus, mainly savers and those with financial deficit mainly borrowers and investors (Manasseh et al, 2021). They aggregate funds on behalf of the borrowers and investors while also facilitating settlement of business transactions.…”
Section: Issn: 2616-4965 11 Background Of the Studymentioning
confidence: 99%
“…It means that the Indonesian sharia stock index trading value is influenced by the Indonesian sharia stock index trade value itself a month ago, and is influenced by the market capitalization on the stock exchange a month ago, where each increase of 1 trillion Indonesian sharia stock index trading values this month is due to the tendency of the increase in market capitalization last month by 0.35 trillion. The negative Indonesian sharia stock index value is suspected because investors are more dominant in seeing the magnitude of the market capitalization value instead of seeing the specific trading value of sharia stocks when trading on the Islamic capital market (Manasseh et al, 2018).…”
Section: The Estimation Of Vector Error Correction Modelmentioning
confidence: 99%
“…From the two impulse response tests above it can be said that the shock given by the market capitalization gives much greater effect than Indonesian sharia stock index. This means that if there is a change in the market capitalization value on the Indonesia stock exchange then the sharia stock index trading value will respond strongly in the second and third month before then heading to a new stable condition (Manasseh et al, 2018).…”
Section: Impulse Response Function Testmentioning
confidence: 99%
“…The variables used are credit to private sector, broad money supply, interest rate and lending rate, RDGP. Using Vector error correction model, the study showed that there is a significant relationship between financial intermediation indicators and economic growth.2.12 LITERATURE GAPSeveral studies (such asJohn and Nwekemezie, 2019; Iwedi, Okey-Nwala, Kenn- Ndubuisi & Adamgbo, 2016; Ekong & Okon, 2016;Usman, Alimi and Onayemi, 2018; Manasseh, Okoh, Abada, Ogbuabor, Alio, Lawal, Nwakoby, &Asogwa, 2021 andAye, 2015) were carried out on financial intermediation variables using variables such as broad money velocity and credit to private sector. The focus has been almost entirely on bank based financial intermediation measures, while ignoring the possible impact of nonbanking influence such as capital market development on Nigerian economy.…”
mentioning
confidence: 99%